The Multiple Role of Korean Missionaries in the Making of Transnational Belonging - Kim, Huiyǒn (Religions, 2022)
For decades, Korean denominations have sent missionaries around the world. While trying to convert people, notably in Southeast Asia, they are currently involved in humanitarian works but also in organizing labor migration and helping migrants during their stay in South Korea. A close study of missionaries’ work reveals the logic underlying the construction of religious transnational networks. Korean missionaries interlace different kinds of ties with various populations of Southeast Asia and adapt their spiritual and material offerings to different situations. This analysis based on multiple fieldwork assessments in Southeast Asia and in South Korea places emphasis on their specific role as transnational actors and on how they use and promote transnational belonging among marginalized populations.